Utilisation of mobile technology in logistics - Ahtola, Laura (My University, 2018)
Accessing information quickly has become more and more important. Mobile devices can nowadays be used to perform and accomplish tasks more efficiently. Logistics companies can benefit from mobile applications in many ways. Many logistics areas, such as warehouse managing and transportation, concentrate on the physical movement of goods. The benefits of mobile applications are emphasised in those environments where portability and real-time information are of great use. The business IT alignment framework offers an approach to researching companies business and IT strategies and execution. The enterprise mobile applications may bring many advantages but also disadvantages to organisations utilising them. In this thesis, the business It alignment framework is used in the context of researching the utilisation of enterprise mobile applications in the case organisations. The utilisation of mobile applications in logistics is studied in this research by using the qualitative research method. Research data has been gathered from semi-structured interviews with case company employees responsible for logistics mobile application projects. The logistics areas where mobile applications are used are warehouse management and transportation. A new logistics IT alignment measurement tool was developed for the purposes of this study, as no such a tool existed before. The tool utilises the previous business IT alignment literature. Companies or researchers can utilise this tool in determining their logistics IT alignment level. This study finds that there are multiple important features that companies should take into account when developing and implementing logistics mobile applications. Ease of use and user friendliness are the most important of them. In addition, information quality and efficiency and effectiveness should be considered. Many companies also benefit from end device independence. Companies can get many advantages from logistics mobile applications. These advantages are for example better information quality, real-time information and cost reductions by consuming less paper. High logistics IT alignment supports in gaining these advantages.
Keywords: supply chain management, logistics, mobile technology, business IT alignment